Hannah Arendt: importance of the historical and fictional stories as a route for ethical and political reflection - Fonnegra Osorio, Claudia Patricia (Estudios de Filosofía, 2017)
This article presents the importance given by Hannah Arendt to historical and fictional stories as a way for ethical and political reflection. It studies, firstly, how stories enable the configuration of identity, of both a man and a community, because the narrative allows to give meaning to the fragility and contingency of human actions. In second place, it analyzes how the narrative allows keeping actions in the memory so they are not forgotten. Finally, it studies how the follow-up of stories contributes for understanding of the human world and strengthening the faculty of judging, for overcoming solipsism, a necessary element for the exercise of an ethical and political conception based on the recognition of human plurality.